New Theories of the Multinational Enterprise. - Rugman, Alan (Routledge Library Editions: International Business., 2013)
This book brings together the work of noted authorities in the field of multinational enterprises who explain and debate the merits of internalization theory as the new general theory of the multinational enterprise. Alternatives to internalization, such as licensing, joint ventures and other contractual arrangements are also evaluated. There are many applications to actual businesses, such as in the hotel, fish, food and banking industries. Also considered are regional office location and applications of the theory to Canada, Japan, the former Yugoslavia, the UK and USA.